FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MALARIA PADA BALITA DI NANGA DEDAI KABUPATEN SINTANG KALIMANTAN BARAT - Dani Suryaningrat (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2018)
This Aims study the factors related with the incidence of malaria Children in the  Dedai of Sintang District. Observated analytic and cross sectional study design. analysis is univariate, bivariate and statistical test using Chi-square with 95% confidence level and 5% significance level then continued with Odds Ratio to the  related. The result correlation between parent knowledge with malaria incidence children, parent attitude with malaria incidence children, between the behavior of the parents and the incidence of malaria children, between ventilation and malaria incidence children, there not correlation between parent education and malaria incidence children, between parent's b with the incidence of malaria children Dedai sintang district.